Phenotypic Overlap of Roberts and Baller-Gerold Syndromes in Two Patients With Craniosynostosis, Limb Reductions, and ESCO2 Mutations - Colombo, Elisa Adele; Mutlu-Albayrak, Hatice; Shafeghati, Yousef; Balasar, Mine; Piard, Juliette; Gentilini, Davide; Di Blasio, Anna Maria; Gervasini, Cristina; Van Maldergem, Lionel; Larizza, Lidia (Frontiers in Pediatrics, 2019)
Baller-Gerold (BGS, MIM#218600) and Roberts (RBS, MIM#268300) syndromes are rare autosomal recessive disorders caused respectively by biallelic alterations in RECQL4 (MIM*603780) and ESCO2 (MIM*609353) genes. Common features are severe growth retardation, limbs shortening and craniofacial abnormalities which may include craniosynostosis. We aimed at unveiling the genetic lesions underpinning the phenotype of two unrelated children with a presumptive BGS diagnosis: patient 1 is a Turkish girl with short stature, microcephaly, craniosynostosis, seizures, intellectual disability, facial telangiectasia, bilateral radial and thumb aplasia, tibial hypoplasia and pes equinovarus. Patient 2 is an Iranian girl born to consanguineous parents with craniosynostosis, micrognathism, bilateral radial aplasia, thumbs and foot deformity in the context of developmental delay. Upon negative RECQL4 test, whole exome sequencing (WES) analysis performed on the two trios led to identify two different ESCO2 homozygous inactivating variants: a previously described c.1131+1G>A transition in patient 1 and an unreported deletion, c.417del, in patient 2, thus turning the diagnosis into Roberts syndrome. The occurrence of a Baller-Gerold phenotype in two unrelated patients that were ultimately diagnosed with RBS demonstrates the strength of WES in redefining the nosological landscape of rare congenital malformation syndromes, a premise to yield optimized patients management and family counselling.